Does grade configuration matter for school performance? Short- and long-run effects of school reorganisation - Helena Holmlund; Anders Böhlmark (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2017)
This paper studies the effects of school organisation on short- and long-run pupil outcomes, exploiting a policy change that reorganised Swedish middle school education. The reorganisation induced pupils to remain in small local schools throughout grades 1-9, as opposed to making a transition to large middle schools between grades 6 and 7. We find that the reorganisation had large consequences for pupils, who came to attend smaller schools closer to home, whose teachers had lower qualifications. Despite that the previous literature has found that school transitions and school size are important inputs in the education production function, we find no evidence that remaining in a small local school and avoiding a transition to a large middle school had effects on educational outcomes. We reconcile our evidence with the previous literature using a survey which shows that Swedish pupils do not perceive large differences in the school environment between schools of different grade configurations.
Keywords: H52; I21; I28; 330; Grade configuration; educational production; school transitions; school size